PENGGUNAAN MEDIA AUDIO VISUAL DALAM PEMBELAJARAN PAI KELAS VII DI SMP NEGERI 2 MAOS KABUPATEN CILACAP TAHUN 2022 - Mahbub Rais Abdurrohim (Jurnal Tawadhu, 2023)
This research is an experimental research in the form of Quasi Experimental Design Type Nonequivalent Control Design which uses experimental groups and control groups. The experimental group was given treatment using audio-visual media, while in the control group it was not treated using audio-visual media but using a conventional learning method, namely lectures. The variables of this study consist of 2 variables, namely free variables and bound variables. The free variable is the effectiveness of the use of audio-visual media while the bound variable is the learning process of PAI class VII. As for the entire population of this study, namely all grade VII students of SMP Negeri 2 Maos and the research samples are class B and Class G. Data collection techniques use Test, Observation and Documentation. Data analysis techniques use t-tests to test the effect of the use of audio-visual media on the effectiveness of the PAI learning process. The results of this study showed that the calculation according to the average posttest value of the experimental group was 75.34 higher than the control group of 68.22. The results of the data analysis showed that the significance value of the hypothesis test using the t-test, namely the independent sample t test obtained a Significance value of 0.033 ? 0.05, therefore it can be blunted that H_o rejected and H_a accepted, which means that there is a positive influence on the use of audio-visual media on the effectiveness of the PAI learning process in class VII at SMP Negeri 2 Maos.